I puritani [melodramma serio in tre parti] - Bellini, Vincenzo 1801-1835 (Deutsche Grammophon, 2007)
During the English Civil War of the 1640's, a Puritan bride goes mad when she feels betrayed by her Royalist bridegroom
Liveaufn.: Met, 6. Januar 2007. - Video production directed by Gary Halvorson. - Bonus: Backstage at the Met with Anna Netrebko, Renée Fleming & Beverly Sills. - Interpr.: Anna Netrebko, soprano. Maria Zifchak, mezzo-soprano. Eduardo Valdes, Eric Cutler, tenors. Franco Vassallo, baritone. Valerian Ruminski, John Relyea, basses. The Metropolitan Opera Orchestra, Chorus and Ballet. Patrick Summers, conductor
Keywords: Operas; DVD-Video; Filmed operas